Effect of Training and Visit System on Professionalization of Extension Agents in Osun State Agricultural Development Programme of Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was carried out to examine the effect of training and visit system on professionalization of extension agents in Osun State Agricultural Development Programme of Nigeria. Seventy-five data were collected by interviewing extension agents constituted the sample size and were interviewed through the aid of using a well-structured questionnaire and information obtained were analyzed using frequency counts, percentages and person correlation coefficient was used for testing the research hypothesis. The findings revealed that 80% of the respondents were between the age group of 30 -50 years, spent between 10 30 years in service (84%) and are married (98.7%). A large proportion (56%) of the respondents holds higher national diploma in general agriculture, exhibited favorable attitude towards the farmers (93.3%), specials in general agriculture (34.7%) and required training in one or more areas of agriculture (69.3%). Analysis performed shows that all the characteristics had positive relationship with effect of training and visit on professionalization of extension agents except years of service, which had a negative relationship though all characters were statistically insignificant. Hence, the more the numbers of years spent on the job the more experience you would be. Which indicated that personal characteristics of the respondent influenced the professionalization of the extension agents through training and visit system? DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13993 Int. J. Agril. Res. Innov. & Tech. 2 (1): 37-41, June, 2012